Investigation of Boron Addition on Densification and Cytotoxicity of Powder Injection Molded 316L Stainless Steel Dental Materials - Aslam, M.; Ahmad, F.; Yusoff, P.S.M.B.M.; Chai, Wen Lin; Ngeow, Wei Cheong; Nawi, M.K.A. (Springer Verlag (Germany), 2016)
Powder injection molding (PIM) is a hybrid of powder metallurgy and plastic injection molding. It is used to develop metallic molded parts with intricate shapes and with improved properties compared with those offered by their wrought counterparts. PIM dental implants should exhibit biocompatibility, high density, good dimensional control, homogeneous properties and low manufacturing cost. In order to achieve these properties, the effect of boron (additive) addition on sintered density and of process effects on the biocompatibility of sintered implants was studied. In activated sintering, additives are used in small quantities to modify the sintering behavior of stainless steel. A constant amount of nanosize elemental boron (0–1.5 wt%) was admixed with 316L stainless steel and was compounded with complex binder to develop feedstocks using a z-blade mixer. Optimal solvent debinding parameters followed by an optimal sintering cycle played a vital role in the development of biocompatible and densified 316L stainless steel dental implants. Although all boron-containing formulations were injection-molded successfully, only PWA-0.5B-1230 samples were able to retain their shapes after sintering. It was concluded that 0.5 wt% addition of elemental boron favored the formation of 316L stainless steel with a sintered density of up to 98.5 % through the formation of a complex iron boride compound (B6Fe23) on the grain boundaries during the sintering process. The formation of a passive layer on the outer surface of implants was controlled using optimal sintering parameters. In in vitro analysis, the cytotoxicity assessment of sintered dental implants materials was determined using the direct and indirect contact techniques.